2004
DOI: 10.1002/eji.200424919
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of the Mill family: a rapidly evolving MHC class I gene family

Abstract: Mill (MHC class I-like located near the leukocyte receptor complex) is a novel family of class I genes identified in mice that is most closely related to the human MICA/B family. In the present study, we isolated Mill cDNA from rats and carried out a comparative genomic analysis. Rats have two Mill genes orthologous to mouse Mill1 and Mill2 near the leukocyte receptor complex, with expression patterns similar to those of their mouse counterparts. Interspecies sequence comparison indicates that Mill is one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…Our previous work has revealed several unique features of this class I family (19,20). First, not all mammalian species have the MILL family; although mice and rats have this family, it is absent in humans.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous work has revealed several unique features of this class I family (19,20). First, not all mammalian species have the MILL family; although mice and rats have this family, it is absent in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, RT-PCR analysis indicated that the members of the MILL family are poorly transcribed in most adult tissues, suggesting a role other than conventional Ag presentation. Sixth, sequence comparison of rat and mouse MILL molecules revealed that Mill is one of the most rapidly evolving class I gene families, and that, in both Mill1 and Mill2, non-synonymous substitutions occur more frequently than synonymous substitutions in the ␣1 domain whereas the opposite is the case in the ␣2 and ␣3 domains, suggesting that the ␣1 domain may be under positive selection (20). Taking all of these points into consideration, we suggested that MILL may perform specialized immune functions required only in certain species or some redundant functions, part of which are executed by other molecules (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the majority of nonclassical class I genes located in the MHC show reasonably high sequence similarity to classical class I genes with the exception of MICA/B (Bahram et al 1994) and HFE (the gene for hemochromatosis) (Feder et al 1996), most of those encoded outside the MHC are quite divergent from classical class I genes . Among such divergent class-I-like genes are CD1 , AZGP1 (the gene for zinc-α2-glycoprotein) (Araki et al 1988), FCGRT (the gene for the heavy chain of the neonatal IgG Fc receptor) (Simister and Mostov 1989), PROCR (the gene for the endothelial protein C receptor) (Fukudome and Esmon 1994), MR1 (Hashimoto et al 1995), RAET/ULBP (the genes for retinoic acid early transcripts 1) (Zou et al 1996), and Mill (MHC class-I-like genes located near the leukocyte receptor complex) (Kasahara et al 2002;Watanabe et al 2004). Accumulated evidence indicates that class-I-like genes have diverse functions ranging from specialized antigen presentation (Bahram 2000;Treiner et al 2003;Vincent et al 2003) to the transport of IgG (Simister and Rees 1985) and lipid mobilization and catabolism (Todorov et al 1998).…”
Section: Introductionmentioning
confidence: 99%